Universal Access to Effective Antibiotics is Essential for Tackling Antibiotic Resistance - Daulaire, Nils; Bang, Abhay; Tomson, Göran; Kalyango, Joan N.; Cars, Otto (Journal of Law, Medicine & Ethics, 2015)
The right to health is enshrined in the constitution of the World Health Organization1 and numerous other international agreements. Yet today, an estimated 5.7 million people die each year (Table 1) from treatable infectious diseases, most of which are susceptible to existing antimicrobials if they were accessible. These deaths occur predominantly among populations living in poverty in low- and middle-income countries, and they greatly exceed the estimated 700,000 annual deaths worldwide currently attributed to antimicrobial resistance (AMR).2 Ensuring universal appropriate access to antimicrobials is not only a critical part of realizing the right to health, it is necessary for mobilizing effective collective action against the development and spread of AMR.
Keywords: Universal Access; Antibiotics; Tackling Antibiotic Resistance